ASCENSÃO DE MAGISTRADAS NO JUDICIÁRIO MARANHENSE, IGUALDADE, GÊNERO E PATRIARCADO: uma análise cognitivo-discursiva. - SOUZA, Lidiane Melo de (2022)
Taking as a starting point the fact that women are still significantly underrepresented at all levels and instances of power, such as in the judiciary, particularly in the highest positions, and considering that, at the basis of this career, the growing number of female judges is not reflected in the higher instances of this sphere, the present research proposes to analyze the institutional policy for career progression of the Maranhão judiciary, its compliance with international instruments and the national gender equity plan and its correlation with patriarchy. Therefore, based on the understanding that there are silent barriers related to gender and the culture of patriarchy in this judiciary, interfering with the material realization of the right to equality and hindering the evolution of female judges in their careers, supported by the works of Fraser (1995), Rosenfeld (1998), Butler (1998; 2012), Habermas (2002; 2010), Scott (2005), among others, this study portrays gender discrimination in the light of the right to equality and respect instead, it also discusses intersectionality, highlighting the differences of class, race and gender that are reflected both in the social construction of the image of women subordinated to men, as well as in the inequalities between the sexes and in the male domination marked by imperceptible conceptions which are introjected into thought. Based on the assumptions of cognitive linguistics and studies of conceptual and discursive metaphor, this qualitative research, of a descriptive-exploratory nature, is also anchored in the work of Lakoff and Johnson (1980; 2002) and Cameron and Maslen (2010) for an interpretation, by means of the emergence of metaphors, of the participants' discourse about the existence of gender prejudice concerning the rise of women in the Maranhão judiciary. Considering the understanding of the non-neutral discourse produced by the patriarchal society and inserted in people’s perceptions and manifestations, a corpus was constituted based on the data collected in a semi-structured questionnaire, with open questions, answered by six male magistrates and fourteen female magistrates, to investigate the factors that make it difficult for women to progress at the same pace as men. The metaphors identified in the participants’ discourse, among which IMAGE OF THE MAGISTRATE IS A MIRROR; MATERNITY IS DIFFICULTY; PUBLIC TENDER CRITERIA IS PERSON/PHYSICAL ENTITY; INTIMACY IS PHYSICAL PROXIMITY; MATERNITY IS CENTRALITY; MATERNITY IS WEIGHT; EMOTIONAL STABILITY IS PHYSICAL PROXIMITY; CAREER IS TRAVEL; FREEDOM IS MOVEMENT; WOMAN IS FRAGILITY/ABSENCE OF STRENGTH, reflected the social representations of women with an impact on the Maranhão judiciary and on the reproduction of gender stereotypes that interfere with the possibilities of career evolution by female magistrates. The analysis, confirming the hypothesis initially raised, concluded that the gender implications linked to a given practice or norm not only can be “non-neutral” in a broad sense, but can even be “masculine” in a strict sense, justified by the different social roles that women play and that interfere with their career progression.